Permissible progeny? the morality of procreation and parenting - Hannan, Sarah; Brennan, Samantha; Vernon, Richard 1945- (Oxford University Press, 2015)
This volume contributes to the growing literature on the morality of procreation and parenting. About half of the chapters take up questions about the morality of bringing children into existence. The other half of the volume considers moral and political questions about adoption and parenting. This collection builds on existing literature by advancing novel perspectives on existing debates. It also raises new issues deserving of our attention